Terahertz conductivity of nanograined bulk Bi2Te3 - Han, Jeong Woo; Izadi, Sepideh; Salloum, Sarah; Wolff, Ulrike; Schnatmann, Lauritz; Bhattacharya, Ahana; Asaithambi, Aswin; Matschy, Sebastian; Schlörb, Heike; Reith, Heiko; Perez, Nicolas; Nielsch, Kornelius; et al. (Optics InfoBase Conference Papers, 2022)
Nanograined Bi2Te3 offers a large surface-to-volume ratio, making it an interesting material to employ the high mobility surface states for devices. We present THz spectroscopic measurements to reveal the role of the surface carriers.
CRIS-Team Scopus Importer:2023-03-20